Evaluation of Cell block for the morphological and immunohistochemical canine appendicular osteosarcoma diagnosis - Stephane Cássia Oliveira Rosa Vexenat (2022)
The canine osteosarcoma (OSA) is the most common bone tumor in dog’s worldwide accounting for up to 85% of malignant bone tumors. Cell Block involves the insertion of cytological specimens into paraffin blocks, aiding in the quality of the cytological diagnosis and obtaining reserve specimens for use in other techniques, including immunohistochemistry. This research aimed to evaluate the sensitivity and specificity of the cell block technique in the diagnosis of canine appendicular OSA. Eleven dogs ranging from 8 to 13-years-old with presumed OSA diagnosis were submitted to bone aspirate cytology, cell block and histopathological evaluation. For cell block, bone cytology was performed and the aspirated material were fixed with 1mL of alcohol at 95%, for five minutes in the syringe itself, and then, 9 mL of 10% formalin was aspirated for 24 hours, keeping the syringe positioned upward for cell decantation. Then, the material was routinely paraffin-embedded. Optical microscopically analysis was performed for cytological, cellblock and histopathological slides by three independent pathologists. Additionally, immunohistochemistry (IHC) was performed in samples from cellblock and histopathological evaluation. There was concordance of the cellblock with the histopathology and immunohistochemical labeling of positive osteopontin with high sensitivity and specificity. It was possible to infer that the cellblock technique was effective for OSA diagnosis and had high reproducibility in IHC staining.